"Lancashire Accents, Lancashire Goods and Lancashire Girls": Local Identity and the Image of the Cotton Industry in the Inter-war Period. (3rd July 2017) - Southern, Jack
ABSTRACT: The production of cotton in Lancashire formed an important part of Lancastrian identity, given the dominance of the industry in that area of the North. However, the decline of the industry during the early twentieth century, particularly during the inter-war period, saw the need to promote the industry to the nation. This article will examine how the image of the cotton industry was projected to a wider audience and, in so doing, sought to challenge long-held assumptions of the North. This will include highlighting the role of civic pride, pageantry, and the election of Cotton Queens, which ultimately showed how the sense of place and pride in the cotton industry was a central facet of living through industrial decline.